Digital Zakat in Economic Empowerment and the Achievement of Sustainable Development Goals: An Islamic Economic Law Perspective - Saragih, Eka Junila; Hidayat, Samsul; Zulinda, Nia; Ismail, Moh (Tasharruf: Journal Economics and Business of Islam, 2025)
This study examines the role of digital zakat in promoting economic empowerment and achieving the Sustainable Development Goals (SDGs) through the lens of Islamic economic law. Adopting a normative legal approach and qualitative methodology, the research draws upon academic literature, national legal frameworks, and institutional practices of zakat management in Indonesia. The findings demonstrate that the digitalization of zakat via e-wallets, mobile banking, and online platforms significantly enhances the efficiency, transparency, and outreach of zakat collection and distribution. This transformation enables muzakki to fulfill their religious obligations in a timely, secure, and accessible manner. Furthermore, it facilitates faster disbursement of zakat funds into empowerment-driven social and economic programs aimed at poverty alleviation and sustainable community development. Despite these benefits, challenges persist. Key obstacles include limited digital literacy among both muzakki and mustahik, inadequate technological infrastructure in rural and remote areas, and the absence of specific regulatory guidelines governing digital zakat transactions. From a normative standpoint, it is essential that digital zakat practices adhere to the principles of maqashid shariah, justice (‘adl), trustworthiness (amanah), and accountability (mas’uliyyah), to ensure compliance with Islamic legal and ethical standards. In conclusion, digital zakat, when governed by sharia-compliant frameworks, serves as a powerful instrument of Islamic social finance. It can significantly contribute to inclusive economic growth, enhance access to education, and reduce inequality. Strengthening regulations, improving digital capacity, and fostering institutional collaboration are vital to unlocking its full potential.